2022
DOI: 10.1001/jamaoncol.2022.1472
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cancer Mortality Among Black Individuals in the US From 1999 to 2019

Abstract: ImportanceCancer is the second leading cause of mortality in the US. Despite national decreases in cancer mortality, Black individuals continue to have the highest cancer death rates.ObjectiveTo examine national trends in cancer mortality from 1999 to 2019 among Black individuals by demographic characteristics and to compare cancer death rates in 2019 among Black individuals with rates in other racial and ethnic groups.Design, Setting, and ParticipantsThis serial cross-sectional study used US national death ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…Racial disparities in cervical cancer incidence and mortality have persisted for decades in the United States, representing one of the largest Black-White mortality gaps for any cancer. 24,25 To date, few studies have evaluated these disparities by histologic subtype, particularly with respect to mortality. In line with our current findings, studies have suggested that although cervical SCC incidence rates are highest among Black women, ADC incidence rates are lowest compared with all racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities in cervical cancer incidence and mortality have persisted for decades in the United States, representing one of the largest Black-White mortality gaps for any cancer. 24,25 To date, few studies have evaluated these disparities by histologic subtype, particularly with respect to mortality. In line with our current findings, studies have suggested that although cervical SCC incidence rates are highest among Black women, ADC incidence rates are lowest compared with all racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 17.6 million people have died of COVID-19 worldwide, with 18.9 million currently getting infected daily. 1 In this issue of JAMA Oncology, Lee and colleagues 2 show that people with cancer are vulnerable to SARS-CoV-2 breakthrough infection and COVID-19 hospitalization.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Cancer is currently the second leading cause of death worldwide, and also placed a heavy burden on health care systems as one of the major public health problems that were difficult to administrate ( 1 ). The GLOBOCAN 2020 estimated to account for 19.3 million new cancer cases and almost 10.0 million cancer deaths occurred in 2020 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%